2008
DOI: 10.3354/meps07481
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors that influence the distribution of coral reef fishes: modeling occurrence data for broad-scale conservation and management

Abstract: To manage coral reef species, it is important to identify the factors that determine their distribution inexpensively. We identified the remotely measured environmental factors that are most influential in determining the distributions of coral reef fish species on a regional scale. Logistic regression models for 227 fish species related presence/absence data to 4 remotely determined environmental predictor variables: depth, presence of a land -sea interface, exposure, and the distance to the nearest estuary. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 52 publications
0
43
0
Order By: Relevance
“…In our case, we found that using aerial photos led to overprediction of gypsum springmound sites, and it was only through remotely sensed LANDSAT data that we were able to better predict gypsophyte locality. Remote sensing has previously been shown to be critical in conservation planning for species with distinct habitat requirements (Sellars and Jolls 2007;Beger and Possingham 2008). Remote sensing data also provide an excellent starting point for identifying areas in need of inventory.…”
Section: Useful Predictors In Small-scale Species Distribution Modelingmentioning
confidence: 99%
“…In our case, we found that using aerial photos led to overprediction of gypsum springmound sites, and it was only through remotely sensed LANDSAT data that we were able to better predict gypsophyte locality. Remote sensing has previously been shown to be critical in conservation planning for species with distinct habitat requirements (Sellars and Jolls 2007;Beger and Possingham 2008). Remote sensing data also provide an excellent starting point for identifying areas in need of inventory.…”
Section: Useful Predictors In Small-scale Species Distribution Modelingmentioning
confidence: 99%
“…Similar hydrodynamic influences on reef fishes have been demonstrated in other volcanic archipelagos (e.g. Friedlan-der et al 2003, Beger & Possingham 2008, Krajewski & Floeter 2011, Richards et al 2012. Pais et al (2007) reported significantly higher abundance of carnivorous labrids and serranids in sheltered habitats in the Mediterranean, whereas De Raedemaecker et al (2010) did not find a significant difference for these guilds.…”
Section: Exposure-related Effectsmentioning
confidence: 57%
“…Friedlander et al 2003, Beger & Possingham 2008, De Raedemaecker et al 2010, Krajewski & Floeter 2011 ever, it also shows that the species' trophic ecology shapes such relationships differently. In agreement with other studies, carnivores and planktivores respond positively to bathymetry (Fried lander & Parrish 1998, Bertoncini et al 2010, Krajewski & Floeter 2011, whereas herbivores and omnivores are also more abundant in shallow and intermediate depths (Friedlander & Parrish 1998, Nemeth & Appeldoorn 2009).…”
Section: Environmental Predictors That Influence the Distribution Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Because collecting biological data is labour intensive, difficult and expensive for the large areas relevant to management, these data are often limited and patchy. Where biological data are limited or lacking, predicting patterns of biodiversity using relationships between biodiversity and physical variables can facilitate conservation decision-making (Lehmann et al 2002, Beger & Possingham 2008, Foster & Dunstan 2010.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%